2009
DOI: 10.1097/bot.0b013e3181b013d2
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Nailing Versus Percutaneous Locked Plating of Extra-Articular Proximal Tibial Fractures: Comparison of 56 Cases

Abstract: Neither IMN or PLP showed a distinct advantage in the treatment of proximal extra-articular tibial fractures. Apex anterior malreduction however was the most prevalent form of malreduction in both groups. Additional surgical reduction techniques were frequently needed with IMN, whereas removal of implants seems to be more commonly needed with PLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 27 publications
12
82
0
2
Order By: Relevance
“…Male Female Total P-Value (comparison with present study) VIDYADHARA S et al [1] 39 6 45 0.711 NORK SE et al [15] 28 7 35 1 LINDVALL E et al [16] 17 5 22 1 MEENA RC et al [ Grade of Fracture Present study shows 50% patients with closed fracture, 20%…”
Section: Studysupporting
confidence: 59%
See 4 more Smart Citations
“…Male Female Total P-Value (comparison with present study) VIDYADHARA S et al [1] 39 6 45 0.711 NORK SE et al [15] 28 7 35 1 LINDVALL E et al [16] 17 5 22 1 MEENA RC et al [ Grade of Fracture Present study shows 50% patients with closed fracture, 20%…”
Section: Studysupporting
confidence: 59%
“…#Union Min Max Mean Rate % p-value wrt present VIDYADHARA S et al [1] 12 36 17.2 0.1626 LINDVALL E et al [16] 96 MEENA RC et al [2] 10 30 18.26 94.7 0.1809 PRESENT 12 18 Pain: Present study reported moderate Knee Pain in 7 cases.…”
Section: Closed/openmentioning
confidence: 65%
See 3 more Smart Citations